Expert System For Diagnosis Of Vitiligo Disease Using The Fuzzy Mamdani Method Based On Web-Based - jonas panggabean; Aditiarno Manik (Marqcha Institute, 2021)
Vitiligo is a disease that causes the skin color to fade. Besides being able to attack any area of ​​the skin on the body, this fading color can also occur on the inside of the mouth, eyes, and hair. In this study, an expert system for diagnosing vitiligo has been built, in order to make it easier for patients to find out the level of vitiligo they are suffering from. The problem of this research is how to build an expert system to diagnose vitiligo by implementing Fuzzy Logic using the Mamdani Method, Fuzzy logic is one approach that uses certain stages. The system was built using a structured approach with Use Case, Sequence, and Activity Diagrams as a system design tool